Leaders’ Behaviors Matter: The Role of Delegation in Promoting Employees’ Feedback-Seeking Behavior - Zhang, Xiyang; Qian, Jing; Wang, Bin; Jin, Zhuyun; Wang, Jiachen; Wang, Yu (Frontiers in Psychology, 2017)
Feedback helps employees to evaluate and improve their performance, but there have been relatively few empirical investigations into how leaders can encourage employees to seek feedback. To fill this gap we examined the relationship among delegation, psychological empowerment, and feedback-seeking behaviour. We hypothesised that delegation promotes feedback-seeking behaviour by psychologically empowering subordinates. In addition, power distance moderates the relationship between delegation and feedback-seeking behaviour. Analysis of data from a sample of 248 full-time employees of a hotel group in northern China indicated that delegation predicts subordinates’ feedback seeking for individuals with moderate and high power distance orientation, but not for those with low power distance orientation. The mediation hypothesis was also supported.